Protective Effects of Two Safflower Derived Compounds, Kaempferol and Hydroxysafflor Yellow A, on Hyperglycaemic Stress-Induced Podocyte Apoptosis via Modulating of Macrophage M1/M2 Polarization - Yuanping Li; Dan Zheng; Dayue Shen; Xilan Zhang; Xiaoyun Zhao; Hui Liao (Journal of Immunology Research)
Objective. The primary initiating mechanism in diabetes nephropathy (DN) is hyperglycemia-induced inflammation in which macrophage and podocyte play important roles. The present research is aimed at exploring the effects of kaempferol (Ka) and hydroxysafflor yellow A (HSYA) on classically activated (M1)/alternatively activated (M2) macrophage polarization and podocyte apoptosis under hyperglycaemic conditions in vitro. Methods. (1) RAW264.7 cells were treated with 11.1 mM glucose (NG), 33.3 mM glucose (HG), Ka 4–8 μM, and HSYA 100–200 μM separately. The expressions of inducible nitric oxide synthase (iNOS), tumor necrosis factor- (TNF-) α, mannose receptor (CD206), and arginase- (Arg-) 1 were quantified by Western blotting and real-time quantitative PCR. The collected supernatants from macrophage were named as (NG) MS, (HG) MS, (Ka) MS, and (HSYA) MS. (2) The podocyte survival rate was assessed by Bromodeoxyuridine assay, while TNF-α and interleukin- (IL-) 1β levels were evaluated by Elisa. Results. (1) Compared to the HG group, the Ka and HSYA 100 μM groups decreased iNOS and TNF-α levels and increased Arg-1 and CD206 expressions significantly (protein and mRNA: p<0.05, respectively). (2) The podocyte survival rate of Ka 8 μM was higher than that of HG, and the rates of (Ka) MS and (HSYA 100 μM) MS were higher than that of (HG) MS significantly (all: p<0.05). (3) TNF-α and IL-1β levels of Ka and HSYA 100 μM were significantly lower than those of the HG group, and both levels in the (Ka) MS and (HSYA) MS were lower than those in the (HG) MS group significantly (p<0.05, respectively). Conclusion. The protective effects of Ka and HSYA on podocyte apoptosis under hyperglycemic stress are related to their modulation on M1/M2 polarization and the lowering effects on TNF-α and IL-1β levels.